Don't know much about history : everything you need to know about American history, but never learned - Davis, Kenneth C. (New York : Harper, 2011)
A revised, updated, and expanded edition of the classic anti-textbook uses a question-and-answer format to offer a chronological, informal introduction to American history.
Includes bibliographical references (p. [665]-694) and index.
Keywords: United States -- History -- Miscellanea; Questions and answers